9514 1404 393
Answer:
250 days
Step-by-step explanation:
If the number of drops increases by a factor of 20/8, the expected life will decrease by the inverse of that factor: 8/20.
The expected life is (8/20)(625 days) = 250 days.
4 multiple choice questions
3 answers per question
4 × 3 = 12
<em>12 possible answers total</em>
12 - 4 = 8
<em>8 incorrect answers
</em><em>4 correct answers
</em><em>
</em>3 × 3 × 3 × 3 = 81
<em>
</em><em>81 possible ways they can answer
</em><em>
</em>Only one of those ways is 100% correct.
<em>
</em>81 - 1 = 80
80 ways
Answer:
The value of x is 7 ⇒ 1st answer
Step-by-step explanation:
* Lets revise a fact in the circle
- The two tangents drawn from a point out side the circle are equal
∵ RSTUV is circumscribed about a circle
∴ Each side of the pentagon is a tangent to the circle
- Look to the attached figure to know how we will solve the problem
- Each tangent divided into two parts
# RS = x + y
∵ RS = 8
∴ x + y = 8 ⇒ (1)
# RV = x + n
∵ RV = 12
∴ x + n = 12 ⇒ (2)
- Subtract (2) from (1)
∴ y - n = -4 ⇒ (3)
# ST = y + z
∵ ST = 12
∴ y + z = 12 ⇒ (4)
# TU = z + m
∵ TU = 15
∴ z + m = 15 ⇒ (5)
- Subtract (5) from (4)
∴ y - m = -3 ⇒ (6)
# UV = m + n
∵ UV = 9
∴ m + n = 9 ⇒ (7)
- Add (6) and (7)
∴ y + n = 6 ⇒ (8)
- Lets solve equation (3) and equation (8) to find y
∵ y - n = -4 ⇒ (3)
∵ y + n = 6 ⇒ (8)
- Add (3) and (8)
∴ 2y = 2 ⇒ divide two sises by 2
∴ y = 1
- Lets substitute the value of y in equation (1)
∵ x + y = 8 ⇒ (1)
∵ y = 1
∴ x + 1 = 8 ⇒ subtract (1) from both sides
∴ x = 7
* The value of x is 7
Answer:
f(x) = 3(x - 2)² + 4
OR
f(x) = 3x² - 12x + 16
Step-by-step explanation:
Vertex form of a parabola:
Standard form of a parabola:
Let's find the vertex of this parabola.
In order to find the a-value (vertex form), let's use another point besides the vertex on the parabola.
Using (3, 7) for (x, y), let's substitute this point and the vertex (2, 4) for (h, k) into the vertex form equation and solve for a.
Simplify using PEMDAS.
Subtract 4 from both sides.
Now we have (h, k) and a of the vertex form.
- y = a(x - h)² + k → y = 3(x - 2)² + 4
In order to convert from vertex to standard form, simplify the equation by FOILing.
Distribute 3 inside the parentheses.
Combine like terms.
Therefore, we have the answer:
<u>Vertex form:</u>
<u>Standard form:</u>
Shehaidksj how. usuejejjrjdjdjdjdjjdjdjdjdjdndjdjdjdhjdjdndjd